2016
DOI: 10.1002/jor.23348
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic bone segment tracking to control femoral derotation osteotomy-A saw bone study

Abstract: Correction of rotational gait abnormalities is common practice in pediatric orthopaedics such as in children with cerebral palsy. Femoral derotation osteotomy is established as a standard treatment, however, different authors reported substantial variability in outcomes following surgery with patients showing over- or under-correction. Only 60% of the applied correction is observed postoperatively, which strongly suggests intraoperative measurement error or loss of correction during surgery. This study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In a previous saw bone study we introduced the system and presented results of the system in an in vitro setting. 21 The data of this trial suggested In the present study, the mean deviation of the EMT system to the CT reference measurement was 2.6˚and therefore, almost within the tolerance of the CT measurement error. This indicates that EMT tracking can deliver a precise dimension of the derotation performed in surgery.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In a previous saw bone study we introduced the system and presented results of the system in an in vitro setting. 21 The data of this trial suggested In the present study, the mean deviation of the EMT system to the CT reference measurement was 2.6˚and therefore, almost within the tolerance of the CT measurement error. This indicates that EMT tracking can deliver a precise dimension of the derotation performed in surgery.…”
Section: Discussionsupporting
confidence: 74%
“…Overall 10 derotations in nine patients were used for the evaluation of the EMT system. Mean age at the point of surgery was 23 years (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Because of the design of the study and the requirements of the ethics committee only adult patients were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations